PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN DENGAN MANAJEMEN LABA SEBAGAI VARIABEL INTERVENING (STUDI PADA BANK KONVENSIONAL) YANG TERDAFTAR DI BEI PERIODE 2018-2020 - Kustiani, Kustiani; Sari, Lita Permata; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The purpose of this study was to determine the effect of capital structure on firm value and earnings management as an intervening variable on the IDX for the 2018-2020 period. The population in this study were all conventional banking companies listed on the Indonesia Stock Exchange (IDX) totaling 46 companies. The sampling technique in this study used purposive sampling so that 10 samples were obtained. Data analysis and hypothesis testing in this study used the Structural Equation-Partial Least Square (SEM-PLS) method. The results of hypothesis testing direct and indirect effects using the Smart PLS 3.0 application, direct effect hypothesis testing shows that capital structure has a significant positive effect on earnings management, capital structure has a significant positive effect on firm value, earnings management has a negative but not significant effect on firm value. The results of the indirect effect test show that the capital structure has a negative but not significant effect on firm value through earnings management.